1993
DOI: 10.1148/radiology.186.2.8421748
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder after surgery: MR imaging with surgical validation.

Abstract: To assess the accuracy of magnetic resonance (MR) imaging in the evaluation of the shoulder after surgery, MR examinations were performed in 31 patients before repeated surgery, and MR findings were correlated with the subsequent operative findings. In addition, the MR findings associated with prior surgery were reviewed, including altered structure of the acromion, soft-tissue metal artifacts, a surgical trough in the humeral head, nonvisualization of the subacromial-subdeltoid fat stripe, and intermediate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
6

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 0 publications
2
81
0
6
Order By: Relevance
“…At the time of follow-up, all patients underwent MRI without arthrography on a 1.5-Tesla scanner (Siemens, Erlangen, Germany). Continuity or rupture of the tendon was assessed on coronal oblique T2-weighted and proton density-weighted images as well as short tau inversion recovery sequences according to established MRI criteria [21][22][23] .…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of follow-up, all patients underwent MRI without arthrography on a 1.5-Tesla scanner (Siemens, Erlangen, Germany). Continuity or rupture of the tendon was assessed on coronal oblique T2-weighted and proton density-weighted images as well as short tau inversion recovery sequences according to established MRI criteria [21][22][23] .…”
Section: Imagingmentioning
confidence: 99%
“…who was blinded to clinical data and treatment randomly analyzed the initial MR arthrograms and the follow-up MRIs. The diagnosis of a full-thickness tear was made 23 when there was a fluid-equivalent signal or a visible gap of the supraspinatus tendon in at least one section of the T2-weighted or fat-suppressed sections. The size of the tear was assessed in millimeters in the sagittal and coronal planes with use of the scale available on the examinations on the MR screen.…”
Section: Imagingmentioning
confidence: 99%
“…35 Magnetic resonance imaging may have a tendency to overestimate the re-rupture rate. [36][37][38] Ultrasonography enables better evaluation of tendon thinning with greater accuracy in the assessment of the rotator cuff. 39,40 It is a dynamic evaluation and low-cost procedure.…”
Section: Discussionmentioning
confidence: 99%
“…As is done for the native shoulder, a surface coil should be used for maximum signal-tonoise ratio, and the imaging planes are similar to those of routine shoulder imaging, with axial, coronal oblique and sagittal oblique perspectives. For full-thickness (or complete) recurrent tears confirmed at surgery, Owen et al 4 reported 86% sensitivity and 92% specificity for MRI. However, although the subacromial space and rotator cuff are exquisitely evaluated in the native shoulder, the presence of susceptibility artefact after subacromial decompression and surgical repair might sometimes limit the evaluation of the rotator cuff, especially when modifications to the MRI protocol to reduce artefacts related to metal are not made.…”
Section: Imaging Approachmentioning
confidence: 99%